ENHANCING FINANCIAL TRANSPARENCY IN NON-PROFIT ORGANISATIONS: CHALLENGES AND INTEGRATION OF IFRS FOR SMES, IFR4NPO, AND GRI STANDARDS - RODRIGUEZ-GALINDO, RUTH (2024)
THIS STUDY EXAMINES THE CHALLENGES AND NEEDS FACED BY NON-PROFIT ORGANISATIONS (NPOS) IN COLOMBIA REGARDING THE ADOPTING OF THE INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) FOR SMALL AND MEDIUM ENTERPRISES (SMES), PARTICULARLY FOCUSING ON SECTIONS 3 AND 4. EMPLOYING A MIXED-METHOD APPROACH, THE RESEARCH COMBINES QUALITATIVE AND QUANTITATIVE METHODS. SURVEYS WERE CONDUCTED WITH COLOMBIA NPOS, OFFICIAL DOCUMENTS WERE ANALYSED, AND COMPARATIVE CASE STUDIES WERE PERFORMED. IN-DEPTH INTERVIEWS AND PARTICIPANT OBSERVATION WERE ALSO UTILISED TO GAIN A COMPREHENSIVE UNDERSTANDING OF THE OBSTACLES AND CURRENT PRACTICES WITHIN THE COLOMBIAN CONTEXT. THE FINDINGS REVEAL THAT NPOS IN COLOMBIA ENCOUNTER SIGNIFICANT DIFFICULTIES IN ADOPTING IFRS DUE TO THE COMPLEXITY OF THE STANDARDS, LACK OF SPECIALISED RESOURCES, AND THE NEED FOR SPECIFIC TRAINING. INTERNAL CHALLENGES SUCH AS DEFICIENCIES IN STAFF QUALIFICATIONS AND TRAINING, RESISTANCE TO CHANGE, AND TECHNOLOGICAL LIMITATIONS WERE IDENTIFIED. EXTERNALLY, AMBIGUITIES IN THE LEGAL FRAMEWORK AND DONOR REQUIREMENTS WERE HIGHLIGHTED. THE CASE STUDY ILLUSTRATED THAT, WHILE THERE ARE SIMILARITIES BETWEEN IFRS FOR SMES AND THE IFR4NPO PROJECT, SPECIFIC ADAPTATIONS ARE ESSENTIAL TO ADDRESS THE UNIQUE NEEDS OF NPOS. THIS RESEARCH UNDERSCORES THE NECESSITY OF DEVELOPING ADDITIONAL GUIDELINES OR MODIFYING EXISTING ONES TO ENHANCE THE INTERPRETATION AND APPLICATION OF IFRS IN COLOMBIA NPOS. IT IS RECOMMENDED TO IMPLEMENT PROACTIVE STRATEGIES BASED ON EDUCATION AND LEGISLATIVE REFORM TO IMPROVE THE TRANSPARENCY AND COMPARABILITY OF FINANCIAL INFORMATION. ADOPTING A MORE TAILORED AND SUPPORTED ACCOUNTING FRAMEWORK WILL FACILITATE A MORE RELEVANT AND SUSTAINABLE IMPLEMENTATION, BENEFITING COLOMBIAN NPOS IN THEIR RESOURCE MANAGEMENT AND ACCOUNTABILITY EFFORTS. © 2024 BY AUTHOR(S).